Feasibility for co-utilisation of Carbonated Reactive Magnesia Cement (CRMC) and industrial wastes in circular economy and CO2 mineralisation. (14th March 2022) - Grünhäuser Soares, Erick; Castro-Gomes, João; Sitarz, Mateusz; Zdeb, Tomasz; Hager, Izabela; Hassan, Khaled; Saif Al-Kuwari, Mohammed
Highlights: The feasibility of carbonated reactive magnesia cement mortars embodying wastes was investigated. Seven different wastes sources were used as filler (sand replacement) and/or magnesia replacement. The carbonation took place at the whole volume independently of the waste-based material used. The strength results were impacted by fresh mortars pH, the waste-based material composition, and through the filler effect. Abstract: The increased concern about climate change is leading to the growth of research interest in alternatives to mitigate its effect. Such trend is also observed in the materials and building technologies field, where among the many possible alternatives. Cementitious composites with a lower CO2 footprint have been recently developed to incorporate waste in their composition, with the capability to adsorb CO2 . This study evaluates the feasibility of incorporating seven different wastes sources as filler and/or magnesia replacement in Carbonated Reactive Magnesia Cement (CRMC)-based mortars. CRMC-based mortars were designed to incorporate reactive magnesia and waste powders, by the volume ratio of three to one (sand to paste). The mortar specimens were cast by static compaction pressure and cured through accelerated carbonation curing for 24 h at controlled conditions. The performance of CRMC-based mortars was evaluated by compressive strength and microstructural examination. TG-DTG and FT-IR analysis were used to investigate the carbonation effectiveness through the specimens' volume. The results showed that the designed mortars embodying waste have achieved strength values of 8.5 to 14.6 MPa and the carbonation took place at the whole volume independently of the waste-based material used. The compressive strength results were found to be influenced by the pH of the raw materials. The study demonstrated that CRMC-based mortars have good binding properties with the different wastes investigated with the capability of adsorbing CO2 the surrounding environment into the cementitious matrix. It provides innovative solutions for the circular economy in the construction sector aside to sequestrate carbon within the built environment.